Digital Methods of Delivering Education and Training in Neuropsychology. (31st May 2022) - Van Patten, Ryan; Bellone, John A; Schmitt, Taylor R; Gaynor, Leslie; Block, Cady
Abstract: Objective: High quality and accessible education is crucial to secure the future of neuropsychology. Recent and ongoing advancements include the creation of a taxonomy of education and training, progress in delineating relevant competencies, and an update to the Houston Conference Guidelines. Meanwhile, there is also potential for growth in digital methods of delivering education such as podcasts, webinars, and social media platforms. This paper aims to review the evidence for these three methods and to provide recommendations for implementing them across the continuum of training in neuropsychology, from graduate school through postdoctoral fellowship and continuing education. Method: We reviewed the literature on podcasts, webinars, and social media platforms as educational tools that may be applied to improve learning of brain–behavior concepts and clinical skills. Specifically, we (a) introduce and describe each method, (b) discuss benefits and drawbacks, (c) review the literature on satisfaction and learning outcomes, and (d) provide suggestions for implementation in neuropsychology training programs. Results: Podcasts and webinars have strong evidence for satisfaction and moderate support for improving learning outcomes, with the learning outcome literature suggesting equivalency between podcasts/webinars and traditional methods of education. Social media platforms are associated with high satisfaction, but learning outcome data are scarce. Conclusions: Evidence for podcasts and webinars is sufficient to support implementation into neuropsychology education, whereas social media platforms should be used more cautiously. We provide recommendations of select instances in which trainees and educators can use these methods to improve education in neuropsychology.